2003
DOI: 10.1104/pp.102.018846
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Inactivation of the Methionine S-Methyltransferase Gene Eliminates the S-Methylmethionine Cycle and Increases the Methylation Ratio

Abstract: Methionine (Met) S-methyltransferase (MMT) catalyzes the synthesis of S-methyl-Met (SMM) from Met and S-adenosyl-Met(Ado-Met). SMM can be reconverted to Met by donating a methyl group to homocysteine (homo-Cys), and concurrent operation of this reaction and that mediated by MMT sets up the SMM cycle. SMM has been hypothesized to be essential as a methyl donor or as a transport form of sulfur, and the SMM cycle has been hypothesized to guard against depletion of the free Met pool by excess Ado-Met synthesis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 33 publications
6
65
2
Order By: Relevance
“…SMM is synthesized from Met by Met S-methyltransferase (MMT) and is recycled back to Met by homo-Cys methyltransferase. However, despite the efficient transport capability of SMM, Arabidopsis and maize mmt mutants, which are unable to synthesize SMM, grow and reproduce normally, suggesting a minimal regulatory role for SMM in sulfur transport of at least these two species (Kocsis et al, 2003). Notwithstanding, a recent report (Lee et al, 2008) showed that a mutant Arabidopsis plant overaccumulating Met in its seeds is due to a mutation eliminating the activity of HMT2, one of the three Arabidopsis HMT isozymes that recycle SMM into Met (Lee et al, 2008).…”
Section: Improving Met Content By Genetic Engineeringmentioning
confidence: 99%
“…SMM is synthesized from Met by Met S-methyltransferase (MMT) and is recycled back to Met by homo-Cys methyltransferase. However, despite the efficient transport capability of SMM, Arabidopsis and maize mmt mutants, which are unable to synthesize SMM, grow and reproduce normally, suggesting a minimal regulatory role for SMM in sulfur transport of at least these two species (Kocsis et al, 2003). Notwithstanding, a recent report (Lee et al, 2008) showed that a mutant Arabidopsis plant overaccumulating Met in its seeds is due to a mutation eliminating the activity of HMT2, one of the three Arabidopsis HMT isozymes that recycle SMM into Met (Lee et al, 2008).…”
Section: Improving Met Content By Genetic Engineeringmentioning
confidence: 99%
“…Here, the flux into Met metabolism has not or has only inefficiently been shut down, resulting in an enhanced generation of SMM, which is undetectable in seeds of wild-type plants (Bourgis et al, 1999). This might also keep AdoMet levels low (Kocsis et al, 2003), which is also required for SMM formation explaining the almost unaffected Thr level. The latter might also be kept low by the increased Ile formation.…”
Section: Interactions Of Aliphatic Glucosinolate Biosynthesis With Mementioning
confidence: 99%
“…Although homocysteine methyltransferase is also present in bacteria, fungi, and animals, methionine methyltransferase has been found only in plants (Ranocha et al, 2000). At5g49810, a non-essential gene encodes methionine methyltransferase (EC 2.1.1.12) in A. thaliana (Tagmount et al, 2002;Kocsis et al, 2003). Extensive biochemical characterization, including in vitro enzyme assays and complementation of S. cerevisiae and E. coli mutations (Ranocha et al, 2000;Ranocha et al, 2001), demonstrated that homocysteine methyltransferase (EC 2.1.1.10) is encoded by three A. thaliana genes, At3g25900 (HMT1), At3g63250 (HMT2), and At3g22740 (HMT3).…”
Section: The S-methylmethionine Cyclementioning
confidence: 99%